Heavy Metal Distribution and Policy Impact from Illegal Mining in Sijunjung: A Systematic Review - Amelia, Kiki; Frinaldi, Aldri; Rembrandt, Rembrandt; Aprilliani, Cici; Audia, Washilla; Batubara, Fanny Yuliana; Hatika, Rindi Genesa; Febrina, Cory; Iswahyudi, Abdi (Postgraduate School, Universitas Negeri Padang, 2025)
Illegal gold mining (PETI) in Sijunjung Regency has triggered a severe environmental crisis, characterized by widespread heavy metal pollution from mercury (Hg) and arsenic (As) that threatens ecosystems and public health. To comprehensively assess this issue and evaluate existing management policies, this study conducted a systematic review following the PRISMA 2020 guidelines, synthesizing evidence from 20 empirical studies. The results reveal that heavy metal concentrations in water, sediment, soil, and biota significantly exceed quality standards, with a clear spatial gradient emanating from PETI sites and a worrying increasing trend over time. Concurrently, the evaluation of management policies uncovered critical weaknesses, including institutional fragmentation, low law enforcement effectiveness (achieving only 45% of its target), and an over-reliance on ineffective repressive measures. In conclusion, the findings underscore the urgent need for a fundamental policy shift from a repressive to an integrative and sustainable model. This study proposes an evidence-based framework that combines stringent regulation, real-time monitoring, community-based economic empowerment, and public health interventions to holistically address the root causes and multifaceted impacts of PETI in Sijunjung.